Aplikasi Kamus Kata Serapan dari 3 Bahasa Asing dengan Koneksi Google Speech API - Risqullah, Fahira Khalisyah; Samsudin, Samsudin; Triase, Triase (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Absorption words are words that are absorbed from foreign languages or regional languages which are then integrated into Indonesian so that they become common words for everyday people. However, people do not know that the words we often use are sometimes not native Indonesian words. Balai Bahasa as a unit whose task is to research the development of Indonesian vocabulary also needs a media that can inform the public about the results of its research related to borrowed words, apart from printed books or a large Indonesian dictionary. The most widely absorbed loanwords into Indonesian are Arabic, Dutch, and English. Therefore, the idea was born to build an application that is useful as a source of knowledge for the community and the media to document the results of loanword research for language halls. The application will be built on the Android platform and using the Java programming language, with a SQLite database. Speech Recognition is done by connecting the Google Speech API with the system, so that the percentage of voice detection becomes text is greater. The resulting application is an Android-based loan word dictionary application that contains 3 foreign languages and is equipped with a voice detection feature that is connected to the google speech API.